PENERAPAN PENDEKATAN FOLLOW THE MONEY DAN FOLLOW THE ASSET GUNA MENGOPTIMALKAN PENANGANAN TINDAK PIDANA NARKOTIKA - Widi Wicaksono (2022)
One of the efforts in eradicating narcotics crimes is to give high penalties to narcotics dealers, but this is still not optimal, because with their economic strength they can still control the Narcotics network from inside the prison. Therefore, extraordinary measures are needed to overcome narcotics crime (extra ordinary measures). This study aims to analyze the application of the follow the money and follow the asset approaches in handling narcotics crimes and the application of the follow the money and follow the assets follow the assets approaches in order to be more optimal in the application of narcotics crimes. This study uses a normative juridical approach. The results of the study stated that, the implementation of the follow the money and follow the asset approaches so far there have been some who have done it, but there are still many who have not done it, most of them are still focused on solving predicate crimes (narcotics). Whereas the application of the follow the money and follow the asset approaches can be used as a reference for law enforcement officers as one of the strategies in optimizing the eradication of narcotics. In addition to punishing Narcotics Dealers, they can also cripple the perpetrators economically